Organização e imprensa estudantil no Instituto de Educação Sud Mennucci (1952-1954) - Schweter, Isis Sanfins (2015)
The research consists in investigating the history of the students organization of the Escola Normal Sud Mennucci de Piracicaba, later called the Instituto de Educação Sud Mennucci. This organization created a student s periodical, the paper entitled O Sud Mennucci has published texts written by the students and which associatedschool life to various issues such as curriculum, literary productions, the school routine, the position occupied by the institution in the city, the place of women in society, demands for improvements in school conditions, among others. In about two years duration, the newspaper published ads and began to circulate outside school. The purpose was to understand the dynamics of sociability established between the students around the articulation and production of a school newspaper between the years 1952 to 1954, contributing to the understanding of the students practice in the defined timeline for this research and the school culture of the institution. The sources used were copies of the newspaper Sud Mennucci and some copies of local newspapers. Interviews were also held with the alumni of the institution, participating or not in these organizations with the objective of register the memory that these individuals built from their students career and the school periodical